TECHNOLOGY OF DEVELOPMENT IN THE ICT SECTOR (American Journal of Interdisciplinary Research and Development, 2022)
On the eve of the celebration of the 30th anniversary of the independence of Uzbekistan, the results achieved in all spheres will be summarized and the next plans will be determined. In recent years, the development of Information Technology and Communications has affected many areas of life. The penetration of digitization in all sectors, the development of the top picture plays a big role in the development of the entire industry, especially for the long-term perspective. Great attention is paid to scientific research, IT technology, startup ideas, and computer literacy in the experience of the countries of the world. Only through the achievements of Science and new technologies can achieve high economic growth. If the world-wide discoveries in the last century were made in many ways based on the human potential, then in today's era science is formed with the help of modern ICT. Today, Uzbekistan, which is ranked among the developing countries, is making great strides in all spheres, and these achievements are underpinned by the rapid development of information technologies and telecommunication systems.